Exploring Literary Psychology: Unveiling the Archetypes of Secondary Characters in Tere Liye's Novel 'Hujan' - Arju Susanto; Mohammad Darwis; Lana Nadia; Kurnia Rachmawati; Nisrina Rona Nabilah (Hasanuddin University, 2024)
In literature, characters often reflect real-life individuals, sometimes resembling people known to the author. Likewise, literary settings may mirror real-world environments, creating a sense of familiarity and authenticity within the narrative. The inclusion of authentic elements, particularly genuine human characters, in literary compositions renders them subjects for psychological examination. Such works serve as psychological reflections of the author while also exerting psychological influence on the reader. For instance, the novel